Serum Cytokine Profile in Adalimumab-treated Refractory Uveitis Patients: Decreased IL-22 Correlates with Clinical Responses. (June 2013) - Cordero-Coma, Miguel; Calleja, Sara; Llorente, Milagros; Rodriguez, Esther; Franco, Manuel; Ruiz de Morales, Jose G.
Abstract Purpose: To report the effect of adalimumab on serum cytokines in chronic refractory uveitis. Methods: Prospective study on the effects of adalimumab on serum cytokine levels at different time points in a cohort of 12 refractory chronic uveitis patients. Results were analyzed according to clinical outcomes and compared with systemic steroid-treated recurrent uveitis patients. Results: Before treatment, patients exhibited significantly increased IL-1β, IL-6, TNFα, IL-12 p70, IL-10, and IL-22. Adalimumab significantly decreased IL-6, and IL-12p70 at early time points (after 1 month of treatment). Adalimumab effects on IL-10 and IL-22 appeared later (after 6 months of treatment). IL-1β, IL-17A, and TNFα were not modified at any time point. Only decreased IL-22 serum levels correlated with disease activity (p = 0.011). These effects were not observed in steroid-treated patients. Conclusions: Adalimumab induced drug-specific and time-dependent declines in serum levels of particular cytokines, although only IL-22 correlated with disease activity in 10 out 12 patients.